2009
DOI: 10.1002/cncr.24134
|View full text |Cite
|
Sign up to set email alerts
|

Initial report of the cancer Patient‐Reported Outcomes Measurement Information System (PROMIS) sexual function committee

Abstract: For this report, the authors described the initial activities of the Cancer Patient-Reported Outcomes Measurement Information System (PROMIS)-Sexual Function domain group, which is part of the National Institutes of Health Roadmap Initiative to develop brief questionnaires or individually tailored assessments of quality-of-life domains. Presented are a literature review of sexual function measures used in cancer populations and descriptions of the domains found in those measures. By using a consensus-driven ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 93 publications
1
71
0
Order By: Relevance
“…A more comprehensive review of available measures was published in 2009 (10). The most widely used instrument recently has been the Female Sexual Function Index (FSFI), a 19-item scale with six domains: desire, arousal, lubrication, orgasm, pain, and satisfaction.…”
Section: Measurement Of Sexual Functionmentioning
confidence: 99%
“…A more comprehensive review of available measures was published in 2009 (10). The most widely used instrument recently has been the Female Sexual Function Index (FSFI), a 19-item scale with six domains: desire, arousal, lubrication, orgasm, pain, and satisfaction.…”
Section: Measurement Of Sexual Functionmentioning
confidence: 99%
“…These treatments often cause significant physiological and anatomical changes and complications such as shortened vagina, vaginal dryness and dyspareunia, and consequently have an adverse effect on a women's quality of life and her ability to engage in sexual intercourse (Wilmoth and Spinelli, 2000;Reis et al, 2010). Findings of empirical research have shown that women with cervical cancer often report less sexual interest, a decrease in sexual activity, dyspareunia, lack of lubrication, and low sexual satisfaction (Bergmark et al, 2002;Donovan et al, 2007;Jeffery et al, 2009;Levin et al, 2010;Lammerink et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The primary goal of the original research was to update a conceptual measurement model, which had been developed based on extant literature and focus groups with patients with cancer, 2426 and which would be used to guide item content coverage for the PROMIS Sexual Function and Satisfaction measure version 2.0. 18 Thus, the original analysis was conducted with the goal of refining item content for a self-report measure.…”
Section: Methodsmentioning
confidence: 99%